THE CONCEPT OF MORAL EDUCATION IN THE QUR'AN IN SDIT DARUL HUFFADZ BEKASI REGENCY - Imron Rosadi; Ahmad Junaedi Sitika (Al-Hayat: Journal of Islamic Education, 2021)
This study aimed to explain the concept of al-Qur'an moral education at SDIT Darul Huffadz Bekasi. The research method used by the author is a type of qualitative research through a field research approach, by collecting data or materials related to the theme of the discussion and the problem, taken from trusted sources through structured interviews as well as observation and documentation, then analyzed coherently, describing all aspects involved and contained in the verses of the Qur'an which are interpreted and describe the meaning contained in the Qur'an. To support this research, the author uses supporting sources from other literature such as books, scientific journals, and so on related to the discussion. The study results stated that SDIT Darul Huffadz Bekasi has a character-building program through Islamic Religious Education with the methods used in its implementation, namely the habit method, the exemplary method and the punishment method.